Steve Biddulph's raising girls - Biddulph, Steve (Warriewood, N.S.W. : Finch Publishing., 2013)
There has been a sudden and universal deterioration in girls' mental health, starting in primary school and devastating the teen years. This book is both a guidebook and a call-to-arms for parents. The five key stages of girlhood are laid out so that you know exactly what matters at which age, and how to build strength and connectedness into your daughter from infancy onwards. This book is both fierce and tender in its mission to help girls more at every age. It's a book for parents who love their daughters deeply, whether they are newborns, teenagers, young women. At last, there is a clear map of girls' minds that accepts no limitations, narrow roles or selling-out of your daughter's potential or uniqueness. Steve Biddulph's Raising Girls explores how to help your daughter feel secure, become an explorer, get along with others, find her soul, and become a woman. All the hazards are signposted -- bullying, eating disorders, body image and depression, social media harms and helps -- as are concrete and simple measures for both mums and dads to help prevent their daughters from becoming victims. Parenthood is restored to an exciting journey, not one worry after another, as it's so often portrayed.
Cover subtitle: From babyhood to womanhood - helping your daughter to grow up wise, warm and strong.
Includes bibliographical references.
Keywords: Girls; Child rearing; Parent and child; Australian